Sales Information System Women's Clothes Based on E-Commerce - Maghfiroh Maulani; Priatno; Muhamad Ryansyah; Bilal Abdul Wahid (Jurnal Mantik, 2021)
The development of online shopping websites has increased to date. These developments make ideas as well as solutions for writers to participate in economic progress in the world of information technology. E-Commerce is the right choice for business development that is inclusive of buying and selling activities and is also becoming very fierce competition for businesses in Indonesia today. E-Commerce in general is an online market for buying and selling activities between business owners, customers, and visitors through the internet. As for the increasing trend of Muslim women's clothing that more and more types and models make the writer want to combine these ideas to create a web E-Commerce. Web-Based Muslim Clothing Sales Information System E-Commerce chosen by the author is designed using the Java programming language, which is a high-level object-oriented programming language, using the waterfall model which has steps - Analysis of software requirements analysis, system design programming, testing and supporting and maintaining. In this method, the program is designed because this method is very easy to implement.